GENDER DALAM PERSFEKTIF BUDAYA DAN BAHASA - Abdul Jalil; St. Aminah (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2018)
Language is not as a communication tool, but also as a tool for human to think in an effort to understand the world. The use of language in people's lives is a part that is reflected as a result of culture including the culture of communication. Regarding the relationship between language and gender is never separated from cultural factors, because there are factors that cause the division of roles based on sex, because a language contains concepts, terms, and symbols that indicate appropriate behavior for men and women. This treatment is different due to social behavior and appears in language symbols. Gender in people's lives gives their respective roles, as cultural ideas that define different roles in both the public and domestic spheres. The view of the universalism of dichotomy between men and women originating from nature and culture, as well as differences in domestic and public roles has been aborted by ethnographic evidences, and at the same time opened up new facts that the dichotomy between men and women is relative.